2017
DOI: 10.1111/1467-8268.12301
|View full text |Cite
|
Sign up to set email alerts
|

Inequity in Maternal and Child Health Care Utilization in Nigeria

Abstract: The study assesses the degree and patterns of horizontal inequity in maternal and child health care utilization in Nigeria. Horizontal inequity was estimated using concentration curves and a standardized concentration index, which was decomposed into need and non-need variables to capture the major drivers of inequity in utilization. Maternal and child health care utilization was measured by antenatal visits, skilled delivery and immunization utilization. Four rounds of Nigerian Demographic and Health Survey (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 35 publications
5
25
0
1
Order By: Relevance
“…The later findings are similar to earlier studies that show pro-rich inequalities in maternal healthcare utilization in Ghana [39] and Nigeria [40]. These results provide important evidence that may assist the health stakeholders to redouble their efforts toward achieving the Sustainable Development Goals (SDGs) three targets of reducing the global maternal mortality ratio to less than 70 per 100,000 live births by 2030 [41].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The later findings are similar to earlier studies that show pro-rich inequalities in maternal healthcare utilization in Ghana [39] and Nigeria [40]. These results provide important evidence that may assist the health stakeholders to redouble their efforts toward achieving the Sustainable Development Goals (SDGs) three targets of reducing the global maternal mortality ratio to less than 70 per 100,000 live births by 2030 [41].…”
Section: Discussionsupporting
confidence: 86%
“…This is not surprising because of the wide gap in socio-economic development between the northern and southern parts of the country [ 10 ]. Studies by Obiyan and Kumar [ 5 ] and Nghargbu and Olaniyan [ 40 ] also emphasized that wealth status and education were the major factors driving inequality in maternal healthcare utilization in Nigeria. Nghargbu and Olaniyan [ 40 ], shows that SES rather than the need for healthcare mainly determine demand for maternal healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…19 Our study findings were also comparable with the findings reported in Bangladesh and other similar settings which showed the key reproductive and maternal health services were concentrated among wealthier, more educated, and women from urban areas. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][33][34][35][36] There is inter-regional disparity in the uptake of maternal health services worldwide, with the highest disparity being in Africa and Asia regions. This has huge implications in progress towards attaining SDG targets related to maternal health.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study communicates that it is equally relevant for other platforms to become fully engaged in the same way if MHSs are to be widely disseminated to adolescents. Indeed, accessibility to MHSs is important in increasing awareness, persuading and reminding pregnant mothers from seeking and getting devoted to seeking health services (6). Overall, the findings indicate that maternal health care services are still low in Uganda.…”
Section: Strategies For Improving Access To Maternal Health Servicementioning
confidence: 86%